1990
DOI: 10.1161/01.cir.82.6.2190
|View full text |Cite
|
Sign up to set email alerts
|

Restenosis after balloon angioplasty. A practical proliferative model in porcine coronary arteries.

Abstract: A model of proliferative human restenosis was developed in domestic pigs by using deep injury to the coronary arterial media. Metal wire coils were delivered percutaneously to the coronary arteries of 11 pigs with an oversized, high-pressure (14 atm) balloon and were left in place for times ranging from 28 to 70 days. During placement, the balloon expanded the coils and delivered them securely within the arterial lumen. Light microscopic examination of the vessels confirmed fracture of the internal elastic lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
146
0
10

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(160 citation statements)
references
References 32 publications
4
146
0
10
Order By: Relevance
“…20,21 The femoral approach offers the advantage of bilateral injury and carries less risk of morbidity and mortality compared with the carotid artery. The time course of intimal hyperplasia in the present study is similar to that found in rabbit, 29 pig, 30 and baboon 31 models. The I/M ratios obtained are comparable to those of other animal models.…”
Section: Discussionsupporting
confidence: 89%
“…20,21 The femoral approach offers the advantage of bilateral injury and carries less risk of morbidity and mortality compared with the carotid artery. The time course of intimal hyperplasia in the present study is similar to that found in rabbit, 29 pig, 30 and baboon 31 models. The I/M ratios obtained are comparable to those of other animal models.…”
Section: Discussionsupporting
confidence: 89%
“…The coronary arteries of piglets have previously proved to respond in a similar manner to the human coronary arteries after injuries (21,22). In fact the in-stent neointimal thickness, usually caused within 28 days from an injury, has been described as identical to the human restenotic neointima.…”
Section: Discussionmentioning
confidence: 94%
“…1990). However, this rate can readily be reduced simply by premedication with 650 mg aspirin at least 24h before stent implantation (Schwartz et al 1990) underlining the importance of anticoagulation therapies. For testing novel low or non-thrombogenic stent designs and coatings, we feel that implantation conditions should be deliberately made difficult by withholding antithrombotic drugs, anticoagulants, dextran, or antiplatelet aggregation therapies, except for heparin during the implantation procedure.…”
Section: Discussionmentioning
confidence: 99%